Monsenhor Rios: : A Story of Devotion and Simplicity (Revista Internacional de Folkcomunicação, 2022)
We seek to study and collect data on the life of Monsignor Antônio Rodrigues Paiva e Rios, regarding his actions in life and the ex-voto manifestations that potentiate possible miracles. We make use of empirical research, the exploratory observation of folkcommunicational practices for data collection in order to inventory the collection of pieces from the core of devotion. We used the theoretical foundation and the investigative technique in the search for data available in bibliographies, interviews, internet search engines, reports in common languages ​​and historical traces. We conclude that this folkcommunication process stems from ex-voto manifestations that represent belief and faith in a mystical scenario that validates itself in the construction of subjectivities, where the religious imaginary is characterized as a source of meanings, social bonds and a sense of belonging.
Keywords: Monsignor Rios; Ex-vote; Folkcommunication